Professional C# and .NET - Nagel, Christian (Wrox, 2021)
Get the latest coverage of the newest features in C#9 and .NET 5 In Professional C# and .NET: 2021 Edition, Microsoft MVP for Visual Studio and Development Technologies and veteran developer, Christian Nagel, delivers a comprehensive tour of the new features and capabilities of C#9 and .NET 5. Experienced programmers making the transition to C# will benefit from the author's in-depth explorations to create Web- and Windows applications using ASP.NET Core, Blazor, and WinUI using modern application patterns and new features offered by .NET including Microservices deployed to Docker images, GRPC, localization, asynchronous streaming, and much more. The book also offers: Discussions of the extension of .NET to non-Microsoft platforms like OSX and Linux Explanations of the newest features in C#9, including support for record types, and enhanced support for tuples, pattern matching, and nullable reference types Integrating .NET applications with Microsoft Azure services such as Azure App Configuration, Azure Key Vault, Azure Functions, the Azure Active Directory, and others Downloadable code examples from wrox.com and github.com with online updates for C# 10 and .NET 6 Perfect for programmers with a background in C#, Visual Basic, Java, or C/C++, Professional C# and .NET: 2021 Edition will also earn a place in the libraries of software architects seeking an up-to-date and fulsome treatment of the latest C# and .NET releases.